Answers

2015-05-19T13:02:13+05:30
2(√2+√6)=2√2+2√6
             =√8+√24
  3√2+√3=√18+√3
 
therefore,      (√8+√24)/(√18+√3)
              multiplying (√18-√3) both in denominator and nominator
                                                     =√8(√18-√3)+√24(√18-√3)/(√18)²-(√3)²
                                                     =√144-√24+√432-√72/18-3
                                                     =12-2√6+12√3-6√2/15
                                                    =4(3+3√3-2√2)/15
                                                      =4/15(3+3√3-2√2)
0
2015-05-20T20:42:45+05:30
2(√2+√6)=2√2+2√6
             =√8+√24
  3√2+√3=√18+√3
 
therefore,      (√8+√24)/(√18+√3)
              multiplying (√18-√3) both in denominator and nominator
                                                     =√8(√18-√3)+√24(√18-√3)/(√18)²-(√3)²
                                                     =√144-√24+√432-√72/18-3
                                                     =12-2√6+12√3-6√2/15
                                                    =4(3+3√3-2√2)/15
                                                      =4/15(3+3√3-2√2)
0